INTERNALISASI NILAI-NILAI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BAHASA ARAB DI MADRASAH IBTIDAIYAH AL-KHAIRIYAH PONTANG - Iin Nurul Inayah (CV. ADIBA AISHA AMIRA, 2024)
This research departs from the phenomenon of Arabic teachers who internalize character education values in Arabic language learning as an effort to prevent demoralization and moral decadence among students at Madrasah Ibtidaiyah Al-Khairiyah Pontang. The approach used in this research is a qualitative approach, by trying to construct reality and understand something hidden behind phenomena that are visible on the surface. The results of the research show that the internalization of character education values in Arabic language learning is going well. The application of character education values carried out by Arabic language learning teachers at Madrasah Ibtidaiyah Al-Khairiyah Pontang is very complete, not only regarding the value of honesty, but also related to how they become children who are always used to living disciplined, frugal, thinking critically, behave qanaah, be tolerant, care about the environment, not be arrogant, optimistic, independent, democratic, love the country, care for the environment, care for the social, love of peace, national spirit, be productive, and other characters that are reflected in learning activities.